Weibo interaction in the discourse of internet anti-corruption: The case of "Brother Watch" event. (August 2018) - Feng, Debing; Wu, Xiaoping
Highlights: Weibo interaction is characterized by an overarching sequence: key tweet + responses. Key tweets are designed as newsworthy and authentic messages to engage the audience. Responses are designed to orient to prior tweets while projecting new actions. Responses chime in with key tweets to get oriented-to messages recirculated and reinforced. Abstract: Extant studies have been predicated on the assumption that Weibo interaction plays important roles in the formation and development of Internet anti-corruption, but little attention has been given to how such interaction is locally constructed among Weibo users. Drawing upon analytical tools evolved from Conversation Analysis and Multimodal Discourse Analysis, this study examined a pool of Weibo tweets and responses employed in discussing an Internet anti-corruption event, i.e., the "Brother Watch" event which happened in 2012. The analysis showed that Weibo interaction featured an overarching sequence of "key tweet + responses", wherein key tweets were formulated as newsworthy and authentic messages to engage the audience. Responses were designed to project new meanings and actions while orienting to prior turns. As a result, exposed information became repetitively circulated, amplified and reinforced, and eventually shaped into an online public event.